2023
DOI: 10.3389/fbioe.2023.1147684
|View full text |Cite
|
Sign up to set email alerts
|

The laws and effects of terahertz wave interactions with neurons

Abstract: Introduction: Terahertz waves lie within the energy range of hydrogen bonding and van der Waals forces. They can couple directly with proteins to excite non-linear resonance effects in proteins, and thus affect the structure of neurons. However, it remains unclear which terahertz radiation protocols modulate the structure of neurons. Furthermore, guidelines and methods for selecting terahertz radiation parameters are lacking.Methods: In this study, the propagation and thermal effects of 0.3–3 THz wave interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Ma et al constructed a thermal effect model for the interaction between terahertz and neurons and found that the temperature of neurons increases rapidly during terahertz radiation and stabilizes after a period of time. And, with the increase in the terahertz radiation power, the peak temperature in the neuron also increases [ 76 ]. Thus, terahertz radiation power and time are important factors that affect neurons.…”
Section: The Impact Of Terahertz Radiation On Neuronal Morphology And...mentioning
confidence: 99%
“…Ma et al constructed a thermal effect model for the interaction between terahertz and neurons and found that the temperature of neurons increases rapidly during terahertz radiation and stabilizes after a period of time. And, with the increase in the terahertz radiation power, the peak temperature in the neuron also increases [ 76 ]. Thus, terahertz radiation power and time are important factors that affect neurons.…”
Section: The Impact Of Terahertz Radiation On Neuronal Morphology And...mentioning
confidence: 99%